2022
DOI: 10.1002/tafs.10386
|View full text |Cite
|
Sign up to set email alerts
|

Swimming depths and water temperatures encountered by radio‐archival‐tagged Chinook Salmon during their spawning migration in the Yukon River basin

Abstract: Objective Historically, Chinook Salmon Oncorhynchus tshawytscha have supported important fisheries throughout the Yukon River basin, but dramatic declines in abundance since the late 1990s have resulted in smaller returns, severe reductions in harvests, and difficulties in meeting escapement goals. These observations coincide with major climatic changes in the northern Pacific, characterized by a general warming trend throughout the region. Our objective was to document the migratory patterns of the fish in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Among Yukon River Chinook salmon, no studies have been designed to estimate overall spawning success across the freshwater adult period. Only one large scale radio tagging study has been conducted in the region and it did overlap with a warm year (2004) when archival tags demonstrated that individuals often experienced water temperatures >18°C and occassionally >21°C, but there was no evidence of en route mortality (Eiler et al, 2014(Eiler et al, , 2015(Eiler et al, , 2022. Spawning ground surveys to estimate egg retention and prespawn mortality have occurred occasionally in a few tributaries and reveal that egg retention is common with 45% of females retaining eggs (reviewed by Twardek et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Yukon River Chinook salmon, no studies have been designed to estimate overall spawning success across the freshwater adult period. Only one large scale radio tagging study has been conducted in the region and it did overlap with a warm year (2004) when archival tags demonstrated that individuals often experienced water temperatures >18°C and occassionally >21°C, but there was no evidence of en route mortality (Eiler et al, 2014(Eiler et al, , 2015(Eiler et al, , 2022. Spawning ground surveys to estimate egg retention and prespawn mortality have occurred occasionally in a few tributaries and reveal that egg retention is common with 45% of females retaining eggs (reviewed by Twardek et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the existence of thermal refugia alone may be insufficient if changes to hydrologic flow regimes results in fragmentation of available habitats (Tonina et al, 2022). The mainstem Yukon River does not appear to have thermal refugia (Eiler et al, 2022) and may help explain why Yukon River salmon have been particularly vulnerable to a warming climate.…”
Section: Discussionmentioning
confidence: 99%